Cardiovascular magnetic resonance detects the progression of impaired myocardial perfusion reserve and increased left-ventricular mass in mice fed a high-fat diet. Issue 1 (December 2016) - Naresh, Nivedita; Butcher, Joshua; Lye, Robert; Chen, Xiao; Isakson, Brant; Gan, Li-Ming; Kramer, Christopher; Annex, Brian; Epstein, Frederick
Abstract Background Impaired myocardial perfusion reserve (MPR) is prevalent in obesity and diabetes, even in the absence of obstructive coronary artery disease (CAD), and is prognostic of adverse events. We sought to establish the time course of reduced MPR and to investigate associated vascular and tissue properties in mice fed a high-fat diet (HFD), as they are an emerging model of human obesity, diabetes, and reduced MPR without obstructive CAD. Methods C57Bl/6 mice fed a HFD or a low-fat diet (control) were imaged at 6, 12, 18 and 24 weeks post-diet. The cardiovascular magnetic resonance (CMR) protocol included multi-slice cine imaging to assess ejection fraction (EF), left-ventricular (LV) mass, LV wall thickness (LVWT), and LV volumes, and first-pass perfusion CMR to quantify MPR. Coronary vascular reactivity, aortic atherosclerosis, myocardial capillary density and tissue fibrosis were also assessed. Results Body weight was increased in HFD mice at 6–24 weeks post-diet (p < 0.05 vs. control). MPR in HFD mice was reduced and LV mass and LVWT were increased in HFD mice at 18 and 24 weeks post-diet (p < 0.05 vs. control). Coronary arteriolar vascular reactivity to adenosine and acetylcholine were reduced in HFD mice (p < 0.05 vs. control). There were no significant differences in cardiac volumes, EF, or capillary density measurements between the two groups. Histology showed interstitial fibrosis in HFD and no aortic atherosclerosis in either group. Conclusions C57Bl/6 mice fed a HFD for 18–24 weeks have progressively increased LV mass and impaired MPR with fibrosis, normal capillary density and no aortic plaque. These results establish C57Bl/6 mice fed a HFD for 18–24 weeks as a model of impaired MPR without obstructive CAD due to obesity and diabetes.